A Chrismas Carol - Dicken, Charles; Illustration by Leech, John (Lahore Readings Publishing, 2016)
Uses the classic story of "A Christmas carol" to develop listening comprehension, reading, pronunciation and critical thinking skills in English.
Include Illustration
Keywords: Dickens, Charles, 1812-1870